A Comparison Between a Dynamic and Static Approach to Asset Management Using CAPM Models on the Australian Securities Market - Paul Mazzola; Dionigi Gerace (Australasian Accounting, Business and Finance Journal, 2015)
Despite the capital asset pricing model being one of the most inﬂuential models in modern portfolio theory, it has also been a victim of criticism in numerous academic papers. Its assumptions which seem to be rather unrealistic, have caused many academics to improve the model by relaxing some of its restrictive statements. In this journal article, we compare the performance of an optimal portfolio of securities in the Australian securities market by constructing two theoretical portfolios; one using the capital asset pricing model which uses a single beta throughout a static investment horizon; and another, which allows the optimal portfolio to be rebalanced each week with an adjusted beta. The performance of the two theoretical portfolios is compared to determine the superior model. Overall, findings showed that due to rebalancing of the portfolio, the multiple period model was the superior model based on before and after transaction cost returns.
Keywords: Financial Markets; Efficiency; Portfolio Optimization